PHYLOGENETIC ANALYSIS OF FMDV ISOLATES RECOVERED IN POST-SOVIET STATES AND MONGOLIA IN 2016 - A. M. Timina; N. G. Zinyakov; A. V. Scherbakov; D. A. Lozovoy (Ветеринария сегодня)
Federal Centre for Animal Health (FGBI “ARRIAH", Vladimir, Russia) is an OIE Regional Reference Laboratory for Foot-and-Mouth Disease for Eastern Europe, Central Asia and Transcaucasia and FAO Reference Centre for Foot-and-Mouth Disease for Central Asia and Western Eurasia. The FGBI “ARRIAH's" objectives as a Regional Reference Laboratory/ Centre include continuous FMDV monitoring in post-Soviet states, detection of new genetic virus variants and matching their antigenic properties with antigenic properties of available vaccine virus strains. The paper demonstrates results of phylogenetic analysis of foot-and-mouth disease virus (FMDV) that caused the disease in Armenia, Zabaikalsky Krai (Russia), Middle Asia and Mongolia in 2016. The test results are indicative of the fact that FMD outbreaks in Armenia were caused by the virus belonging to A/G-VII genetic lineage that was widely spread in the Near East in 2015 and had been never reported in post-Soviet states before. The FMD outbreaks in the Zabaikalsky Krai in November -December 2016 were caused by the exotic for Russia FMD virus of O/Ind-2001d genetic lineage. In Middle Asia FMD was caused by O/ME-SA/PanAsia-2 virus belonging to the O/ME-SA/PanAsia-2 genetic lineage and endemic for the region. In Mongolia the FMD outbreak was caused by the virus belonging to A/Sea-97 genetic lineage that had been previously reported in this country in 2013. Results of the virus genotyping are of particular importance for adjustment of the disease control measures.